Le nouveau management public : Levier de performance des établissements publics. - Abbes BENTAJA; Hicham ASSALIH (African Scientific Journal, 2022)
Public organizations are often seen as inefficient, ineffective and less profitable entities, the main reason for this negative observation is due to the various dysfunctions they have been experiencing for years, given their organizational nature and their specific purposes (Charreaux, 2006). The objective of decision makers and politicians is to find ways to improve performance, which remains a major challenge in order to achieve the desired development. In recent years, and with the aim of improving governance and performance, many OECD countries have embarked on a process of modernizing their public management. In addition, several countries are opting for an acceleration of privatization, which calls into question the role of the State, knowing that private companies are more efficient especially in strategic sectors. It is in this perspective of making public organizations effective and efficient, that the Moroccan State has been trying to put in place for years policies aimed at improving the management and performance of public organizations. This article provides an overview of the evolution of the New Public Management approach, the combination of multiple factors of change, the potentials and challenges of its implementation. The focus is on the link between significant reforms and public sector performance. This work aims to clarify the areas, the limits and the practice of the new public management which constitutes leads to follow for the development of the public performances. The purpose is to provide a theoretical reflection on the new public management, and so constituting an appropriate frame of reference for the establishment of a clear, realistic and achievable policy in terms of management of the public organization.